Melacak Otentisitas Hukum Islam Dalam Hadis Nabi (Studi Pemikiran Josepht Schacht) - Mohammad Muhtador (AL QUDS : Jurnal Studi Alquran dan Hadis, 2017)
This article researche Joseph Schacht's idea of Islamic law. As an oriental’s, Schacht has competence in studying Islamic law with history perspective. Schacht's study of Islamic law on the basis of skepticism by historical criticism is a collection of analyzes in the study of the hadith of the Prophet. The conclusion is different from other thinkers. Schacht doubts the authenticity of Islamic law as a product of teaching, the article of Islamic law development cannot be separated from the interests of the ruler.